2020
DOI: 10.1055/s-0040-1715285
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and the Mental Health of Health Care Workers: Awareness to Action

Abstract: The enormity of the coronavirus disease-2019 (COVID-19) pandemic has overwhelmed most health services and has placed health care service providers under unprecedented stress. The rapidity of spread, uncertain clinical course, and unavailability of effective treatment make clinical decisions cognitively demanding. Extended work hours inside uncomfortable protective gears, improper hydration, with conflictual health systems and patients at work; and social stigma and isolation after it ends, have created an unen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…We found that our RADSC sample reported lower burnout and anxiety compared to previous published studies 28 (although direct comparison may not be possible) and to our larger local hospital cohort, despite similar proportions of exposure to suspected or confirmed COVID‐19 cases (a proportion of RADSC staff included within the study had been redeployed to the emergency department and makeshift facilities directly catering to known COVID patient populations; further, RADSC includes radiographers and doctors that normally have frequent patient contact, such as interventional radiologists and nuclear medicine physicians). We also found that job dedication and teamwork were stronger among RADSC staff compared to the larger hospital cohort, with the latter noted to be statistically significant.…”
Section: Discussioncontrasting
confidence: 54%
“…We found that our RADSC sample reported lower burnout and anxiety compared to previous published studies 28 (although direct comparison may not be possible) and to our larger local hospital cohort, despite similar proportions of exposure to suspected or confirmed COVID‐19 cases (a proportion of RADSC staff included within the study had been redeployed to the emergency department and makeshift facilities directly catering to known COVID patient populations; further, RADSC includes radiographers and doctors that normally have frequent patient contact, such as interventional radiologists and nuclear medicine physicians). We also found that job dedication and teamwork were stronger among RADSC staff compared to the larger hospital cohort, with the latter noted to be statistically significant.…”
Section: Discussioncontrasting
confidence: 54%
“…A nationwide lockdown was initiated in many countries, including the UK, Australia, United States, Canada, France, Italy and New Zealand, in March 2020. With a surge in cases, especially amongst older people residing in long‐term care facilities, Health and Social Care Personnel (HSCP) across the world have been thrust into the role of frontline workers in the fight to stem the spread of COVID‐19 and minimise the impact on those infected (Rajhans et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these constituents may be appertained to the workplace in which healthcare professionals operate (Cohen et al, 2020). These outcomes suggest exploring the genesis of mental health problems in HCWs and to practice a precautionary appraisal and curative plan to satisfy their desire (Rajhans et al, 2020).…”
Section: Prevalence Of Moral and Mental Distress Among Covid Warriorsmentioning
confidence: 99%
“…A recent systemic review found that exposure to Covid-19 is the consistently reported source of mental health issues with concern about infecting family and friends (Vindegaard & Benros, 2020). The liable factors included direct exposure to Covid-19 diagnosed patient, working in critical care units, speculative to exposure and being a frontline HCW (Rajhans et al, 2020). Studies reported that unmediated and constant contiguity with infected brings about post-traumatic symptoms, depression, anxiety, insomnia and general mental health issues in contrast with those who had no constant contiguity with infected patients (Alnazly et al, 2021).…”
Section: Risk Of Covid-19 Infection To Self and Near Onesmentioning
confidence: 99%
See 1 more Smart Citation